Diminishing Chromium Use on Combined Chromium-Gambier Tanning Process Upon the Characteristics of Tanned Leather - A Kasim; D Novia; S Mutiar; A efendi (Media Peternakan, 2014)
The research was aimed to investigate the influence of minimizing chromium use on combined chromium-gambier process upon the characteristics of tanned leather. At the first stage of tanning process, chromium was used and in the second stage it was replaced by gambier. The raw material used was dried saline-preserved goat skin. The treatments applied on the tanning process were the different concentrations of chromium ranging from the highest level of 6% to the lowest level of 1% which was then re-tanned by using 8% concentration of gambier. The examination parameters included chemical and physical properties as well as visual investigation on the tanned leather in accordance with SNI-06-0463-1989-A. The result showed that the tanning process by using 2% chromium in the first step and 8% gambier in the second step was a treatment combination producing tanned leather that met the standard. The examination on tanned leather resulted from such treatment showed 56.33% rawhide, 17.45% of bound tannin, 31.22% of tanning level, tensile strength 386.30 kg/cm2, flexibility 31.91%, leather width 1.3 mm, density 0.75 g/cm3, the leather was quite elastic with light brownish color. In conclusion, minimizing the use of chromium in the combined tanning process of chromium and gambier can be implemented to the lowest of 2% chromium concentration and 8% gambier in the first and second step, respectively. Key words: gambier, leather, minimizing chromium, tanning